SDN-Based Satellite Networks:Progress, Opportunities and Challenges - Dan YANG; Jiang LIU; Ran ZHANG; Fangqi LIU; Man OUYANG; Tao HUANG; Yunjie LIU (天地一体化信息网络)
The current research status of SDN-based satellite communication networks was investigated, the SDN-based satellite communication network architecture and related key technical solutions was introduced and discussed; The opportunities and challenges faced by SDN-based satellite networks were discussed.